PENGEMBANGAN E-LEARNING BERBASIS WEB DI SMA YADIKA LANGOWAN - Klaudia Maki; Ferdinand I. Sangkop; Made Krisnanda (JOINTER : Journal of Informatics Engineering, 2023)
E-learning is the utilization of information technology that is applied in the world of education by using electronic media so that learning can be accessed anywhere and anytime. The existence of e-learning is expected to help in the current teaching and learning process. Yadika Langowan High School is one of the high schools in East Langowan, where the teaching and learning process carried out at this school still uses conventional learning so that the teaching and learning process is still focused on learning in the classroom, this is also supported by the Covid-19 which caused the teaching and learning process is limited to only 50% of students who can attend school. This research aims to help the above problems by creating web-based e-learning at SMA Yadika Langowan as an addition or substitute for the current learning process. The method used in this research is Dynamic System Development Method (DSDM). The system modeling uses Unified Modeling Language (UML) modeling. The results of this research are a school website that is integrated with Moodle-based e-learning, for system testing using Blackbox testing and media expert validation.